Ciprofloxacin 1986
DOI: 10.1007/978-3-663-01930-5_4
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Ciprofloxacin and Other 4-Quinolones Against Chlamydia trachomatis and Mycoplasmas In Vitro

Abstract: Ciprofloxacin was found to be the most active of a group of 4-quinolone antibiotics tested against the SA2 f strain of Chlarnydia trachomatis (MBC and MIC 1.0 rag/l). Against genital isolates of Chlamydia trachomatis, ciprofloxacin was twice as active as rosoxacin.Ciprofloxacin showed similar activity to that of oxytetracycline against clinical isolates of Mycoplasma hominis and Ureaplasma urealyticum, and was 8-fold more active than rosoxacin against the latter.Recently, a number of new 4-quinolones have beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
23
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 5 publications
4
23
1
Order By: Relevance
“…A-56619 was the most active quinolone against both the lymphogranuloma venereum and occulogenital strains of C. trachomatis tested, having MICs eightfold lower than those of ciprofloxacin. The isolates were fully resistant to norfloxacin, as previously reported (1,9,10,14,17). The agents showed poor activity against G. vaginalis and U. urealyticum.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…A-56619 was the most active quinolone against both the lymphogranuloma venereum and occulogenital strains of C. trachomatis tested, having MICs eightfold lower than those of ciprofloxacin. The isolates were fully resistant to norfloxacin, as previously reported (1,9,10,14,17). The agents showed poor activity against G. vaginalis and U. urealyticum.…”
supporting
confidence: 72%
“…We found most U. urealyticum strains tested to be resistant to the quinolones. Although lower MICs of ciprofloxacin against U. urealyticum have been reported (14), similar MIC ranges have also been documented (1,8,17).…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Comparison of ciprofloxacin, norfloxacin, pefloxacin, pipemidic acid and a variety of nonquinolone antibacterial agents (nitrofurantoin, sulfamethoxazole, trimethoprim, cephradine and amoxicillin) demonstrated that ciprofloxacin had the broadest spectrum of activity against all gram-negative bacteria and streptococci tested, with the exception of Enterococcus faecalis and Streptococcus pneumoniae (Hoogkamp-Korstanje, 1984). Compared with rosoxacin, norfloxacin, nalidixic acid and oxolinic acid the activity of ciprofloxacin against Chlamydia trachomatis, Mycoplasma hominis and Ureaplasma urealyticum was found to be at least twice as high (Ridgway et al, 1984). Enrofloxacin has structural similarity to ciprofloxacin and has a similar antibacterial spectrum to ciprofloxacin against Haemophilus sp., Pasteurella sp.…”
Section: Spectrum Of Activitymentioning
confidence: 99%